Community-based Rehabilitation Training after stroke: protocol of a pilot randomised controlled trial (ReTrain). Issue 10 (3rd October 2016) - Dean, Sarah G; Poltawski, Leon; Forster, Anne; Taylor, Rod S; Spencer, Anne; James, Martin; Allison, Rhoda; Stevens, Shirley; Norris, Meriel; Shepherd, Anthony I; Calitri, Raff
Abstract : Introduction: The Rehabilitation Training (ReTrain) intervention aims to improve functional mobility, adherence to poststroke exercise guidelines and quality of life for people after stroke. A definitive randomised controlled trial (RCT) is required to assess the clinical and cost-effectiveness of ReTrain, which is based on Action for Rehabilitation from Neurological Injury (ARNI). The purpose of this pilot study is to assess the feasibility of such a definitive trial and inform its design. Methods and analysis: A 2-group, assessor-blinded, randomised controlled external pilot trial with parallel mixed-methods process evaluation and economic evaluation. 48 participants discharged from clinical rehabilitation despite residual physical disability will be individually randomised 1:1 to ReTrain (25 sessions) or control (exercise advice booklet). Outcome assessment at baseline, 6 and 9 months include Rivermead Mobility Index; Timed Up and Go Test; modified Patient-Specific Functional Scale; 7-day accelerometry; Stroke Self-efficacy Questionnaire, exercise diary, Fatigue Assessment Scale, exercise beliefs and self-efficacy questionnaires, SF-12, EQ-5D-5L, Stroke Quality of Life, Carer Burden Index and Service Receipt Inventory. Feasibility, acceptability and process outcomes include recruitment and retention rates; with measurement burden and trial experiences being explored in qualitative interviews (20 participants, 3 intervention providers). Analyses include descriptive statistics, with 95% CI where appropriate; qualitative themes; intervention fidelity from videos and session checklists; rehearsal of health economic analysis. Ethics and dissemination: National Health Service (NHS) National Research Ethics Service approval granted in April 2015; recruitment started in June. Preliminary studies suggested low risk of serious adverse events; however (minor) falls, transitory muscle soreness and high levels of postexercise fatigue are expected. Outputs include pilot data to inform whether to proceed to a definitive RCT and support a funding application; finalised Trainer and Intervention Delivery manuals for multicentre replication of ReTrain; presentations at conferences, public involvement events; internationally recognised peer-reviewed journal publications, open access sources and media releases. Trial registration number: NCT02429180 ; Pre-results.